Novel mutation of the cyclin-dependent kinase 4 gene in a Chinese patient with intimal sarcoma of the pulmonary artery - Gao, Feng; Liu, Qi-cai; Wang, Mi; Wang, Zhi-qiang; Huang, Yi; Zhou, Xiao-hui; Zhang, Sheng (Chinese medical journal, 2009)
The long arm of human chromosome 12 contains a region that has been found to be amplified in a number of different tumors, including osteosarcomas and soft tissue sarcomas. There are more than 5 genes located in this area such as CDK2, CDK4, WNT1, MDM2 and WNTIOb. CDK4 gene consists of eight exons, of which the start codon is located in the beginning of exon 2 and the stop codon in the a member of the Ser-Thr catalytic domain extends beginning of exon 8. CDK4 is protein kinase family and its from amino acid 6 to 295.